The power of the court to grant alternative accommodation orders: an investigation into when an alternative accommodation order as a condition to the eviction of unlawful occupiers in terms of PIE would comply with the court's constitutional mandate - Fick, Sarah Johanna (Department of Private Law, 2018)
In an eviction matter, the court is required to consider all relevant circumstances and grant an order that is just and equitable. An important relevant circumstance to be considered is whether the unlawful occupiers have alternative accommodation. Courts are reluctant to grant eviction orders that would leave the unlawful occupiers homeless. In matters where unlawful occupiers are unable to secure their own alternative accommodation, courts often look to the state to provide alternative accommodation. Courts have ordered the state to provide alternative accommodation to the unlawful occupiers in certain cases as a condition of the eviction order (an alternative accommodation order). This thesis seeks to determine when an alternative accommodation order as a condition to the eviction of unlawful occupiers in terms of the Prevention of Illegal Eviction From and Unlawful Occupation of Land Act 19 of 1998 (PIE) would comply with the court's constitutional mandate. Two criteria are determined against which to test whether alternative accommodation orders comply with the court's constitutional mandate. First, the court's constitutional mandate requires that its orders adhere to the existing legal framework. Second, the court's constitutional mandate requires that its orders respect the functions of the branches of government. An alternative accommodation order would only adhere to the legal framework if there is a valid ground for placing this duty on the state. The possible grounds for holding the state liable relate to its constitutional duty to respect, protect, promote and fulfil human rights. One possible ground relates to the state's duty to fulfil the unlawful occupiers' right of access to adequate housing by implementing reasonable short-term housing programmes. Hence, whether the state has a duty to accommodate the unlawful occupiers within its short-term housing programme is a relevant circumstance to be considered by the court. A finding that the state has a duty to accommodate the unlawful occupiers, immediately, is likely to lead to an eviction with an order against the state to provide alternative accommodation, regardless of the other circumstances. If the state does not have a duty to accommodate the unlawful occupiers immediately in terms of its duty to fulfil human rights, its liability to provide alternative accommodation might still be found on its duty to respect and protect human rights. This is because, under some circumstances, the granting of an eviction order that results in homelessness might violate the rights of the unlawful occupiers, whereas a denial of the eviction or a delay in the granting or execution of an eviction order might violate the rights of the landowner. Placing the duty on the state to prevent or mitigate the violation by compensating either of the parties could be justified due to the state's duty to respect and protect human rights. As an alternative to compensation, a court could order the state to provide alternative accommodation to the unlawful occupiers. These two possible grounds for alternative accommodation orders are analysed to determine when alternative accommodation orders based on these grounds would adhere to the existing legal framework and respect the functions of the branches of government. These grounds are likely to have the same outcome. For both grounds, certain factors weigh heavily against an alternative accommodation order: blameworthiness on the part of the unlawful occupiers, a lack of blameworthiness on the part of the state, a finding that the state's limited resources should rather be spent on others who are needier or more deserving. In the conclusion of the thesis, recommendations are made regarding two problem areas in granting alternative accommodation orders in eviction matters - the availability of state resources and the burden of proof.